Future Era of Accountants under the Impact of AI - Guan Ran (SHS Web of Conferences, 2025)
The integration of Artificial Intelligence (AI) in accounting is transforming the profession by automating tasks such as fraud detection, financial forecasting, and risk assessment, enhancing efficiency and accuracy. As AI reshapes the industry, accountants must develop expertise in data analytics, predictive modeling, and cybersecurity to remain competitive. CPA Canada and AICPA have incorporated AI governance and digital risk management into certification programs to equip accountants for this shift. The Big Four accounting firms—Deloitte, PwC, KPMG, and EY—are leading AI adoption, implementing AI-driven auditing, contract risk analysis, and predictive analytics to improve compliance and decision-making. However, AI also introduces challenges related to transparency, cybersecurity, and regulatory oversight. Future opportunities in accounting include AI-driven predictive analytics, blockchain, and big data analysis, opening new career paths. Yet, concerns persist regarding job displacement, data security, and algorithmic bias. Regulatory bodies are updating IFRS, GAAP, and GDPR to address AI-related risks in financial reporting. To adapt, accountants must embrace AI responsibly, ensuring financial transparency, compliance, and ethical decision-making in an evolving digital landscape.